Redistributive effects of pension reforms: Who are the winners and losers? - Miguel Sanchez-Romero; Philip Schuster; Alexia Prskawetz (TU Wien, Institute of Statistics and Mathematical Methods in Economics, Research Unit in Economics, 2021)
As the heterogeneity in life expectancy by socioeconomic status increases, pension systems become more regressive implying wealth transfers from short to long lived individuals. Various pension reforms aim to reduce these inequalities that are caused by ex-ante differences in life expectancy. However, these pension reforms may themselves induce redistribution effects since a) life expectancy is not perfectly correlated to socioeconomic status and b) pension reforms themselves will have an impact on life cycle decisions (education, consumption, health, labor supply) and ultimately also on life expectancy and the composition of the population. To account for these feedback effects of pension reforms in heterogenous aging societies we propose an OLG framework that is populated by heterogeneous individuals that initially differ by their learning ability and disutility from the effort of attending schooling. These initial heterogeneities imply differences in ex ante life expectancies. Within this framework we study two pension reforms that aim to account for these differences in ex ante life expectancies. We show that by including the feedback of pension reforms on individual behavior, new redistributions may result.
Keywords: 330; Overlapping generations; Mortality and fertility differentials; Inequality; Life cycle; Pensions; Progressivity